Flow and Heat Dissipation Analysis in Transformer Substation with Minimal Ventilation using CFD - Bahri, Farid Akmal Saipul; Hasini, Hasril (International Journal of Engineering and Technology, 2018)
This paper aims to investigate the flow and heat dissipation of a transformer located in substation building with minimal ventilation system. The study is carried out using CFD, which model the flow and conjugate heat transfer in step-up transformer and its surrounding air. Transformer model is generated by considering the extended fins at both side which enhance heat dissipation. Three different substation ventilation designs are proposed in this work. The effect of air outlet positions with fixed inlets are investigated. The primary objective is to investigate transformer surface and surrounding temperatures for different ventilation systems. The result indicated that minimum natural ventilation of a transformer substation is achievable to avoid transformer overheating. This must be achieved by carefully selecting suitable air inlets and outlets positions in a transformer substation.